IMMU-43. RNA-MODIFIED T CELLS AS A NON-INVASIVE AND EFFICACIOUS STRATEGY TO DELIVER THERAPEUTIC MACROMOLECULES LOCALLY TO INTRACRANIAL TUMORS. (5th November 2018) - Pohl-Guimaraes, Fernanda; Yang, Changlin; Dyson, Kyle; Wildes, Tyler; Drake, Jeffrey; Huang, Jianping; Flores, Catherine; Sayour, Elias; Mitchell, Duane
Abstract: INTRODUCTION: With the presence of the blood-brain barrier (BBB), successful drug delivery to central nervous system (CNS) malignancies remains a challenge. By inducing tumor regression and potentiating immune responses, cytokines, such as granulocyte macrophage colony-stimulating factor (GM-CSF), have shown promise as a biological agent to enhance anti-tumor efficacy in preclinical studies and cancer immunotherapy trials. However, intravenous cytokine delivery has limited access to CNS, and are often associated with significant systemic side effects. To bypass limitations of systemically administered cytokines, we investigate the HYPOTHESIS that RNA-modified T cells can deliver macromolecules directly to intracranial tumors. Since activated T cells have an inherent ability to cross the BBB and lyse tumor cells, this strategy makes them an attractive biological carrier for cancer cell therapy. METHODS: Using electroporation to deliver messenger RNA (mRNA) to T cells, we evaluated GM-CSF secretion and the function of GM-CSF RNA-modified T cells. RESULTS: We demonstrated that activated T cells could be modified to secrete GM-CSF protein in vitro, while retaining their inherent effector functions. In a murine intracranial tumor model, GM-CSF RNA-modified T cells effectively delivered GM-CSF to the tumor microenvironment in vivo, and significantly extended median overall survival with long term cures in some treated animals. Importantly, GM-CSF expressing T cells demonstrated a superior anti-tumor efficacy compared to unmodified T cells, and systemic administration of recombinant GM-CSF provided no treatment benefit when co-delivered with unmodified T cells. Such anti-tumor effects were associated with increased interferon gamma secretion locally within tumor microenvironment, and systemic antigen-specific T cell expansion within secondary lymph nodes. CONCLUSIONS: This study strongly supports the implementation of a non-invasive and efficacious strategy to deliver therapeutic macromolecules locally to invasive brain tumors, while offers potential widespread applicability for the delivery of biological agents to other CNS conditions, such as neurodegenerative or neuroinflammatory diseases.